Experimental Study on Exterior Precast Concrete Frames under Column Removal Scenarios - Kang, Shaobo (2016)
With rigid boundary conditions, precast concrete beam-column subassemblages are capable of initiating significant compressive arch action (CAA) and catenary action under column removal scenarios. However, axial force in these bridging beams over the middle column removal may induce flexural or shear failure of adjacent side columns, which in turn hinders the full development of CAA and catenary action in beams. Thus, it is necessary to assess structural behaviour of precast concrete frames subject to column loss. This paper presents an experimental investigation on the resistance and failure mode of two precast frames. Each frame incorporates a middle beam-column joint, a double-bay beam, and two side columns. Specimens were loaded by a vertical servo-hydraulic actuator on the middle joint, and their reaction forces were recorded by a horizontal load cell on the top and a pin support at the bottom of each side column. Test results and observations indicate shear failure of the side beam-column joint, as well as bar fracture in the beam-column joint under CAA and catenary action. Conclusions from the frame tests suggest that the side columns have to be strengthened so as to protect them from potential failure under middle column removal scenarios.